P-region element reinforced double-monatomic catalyst as well as preparation method and application of P-region element reinforced double-monatomic catalyst
By introducing p-block element gallium to traditional transition metal single-atom catalysts, double-single-atom catalysts are prepared, which solves the problems of poor selectivity and high cost in the electrocatalytic di-electron oxygen reduction process, and achieves efficient and low-cost hydrogen peroxide production.
Patent Information
- Application Number
- CN202411775650.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-05
AI Technical Summary
In the prior art, traditional single-atom catalysts based on transition metals have poor selectivity and high cost in the electrocatalytic di-electron oxygen reduction process, which limits their large-scale application.
By introducing p-block elements, such as gallium, to collaborate with traditional transition metals to prepare a double single-atom catalyst, adjusting the microenvironment of the catalyst and the intermediate fracture mode during oxygen reduction.
The selectivity and yield of hydrogen peroxide are significantly improved, the cost of catalyst is reduced, and the poor performance problem of traditional catalysts in the process of di-electron oxygen reduction is solved.
Smart Images

Figure CN119553308A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalytic hydrogen peroxide production, and specifically relates to a P-zone element-enhanced double single-atom catalyst, a preparation method thereof, and an application of the catalyst as a catalyst for electrocatalytic hydrogen peroxide production. Background Art
[0002] As a green oxidant, hydrogen peroxide (H2O2) has a wide range of applications in the fields of medicine, textiles and environmental catalysis. At present, the synthesis of high-concentration (>37%) H2O2 mainly adopts the highly polluting anthraquinone process, which has the disadvantages of high energy consumption, complex process and high transportation risk. Therefore, more economical and environmentally friendly production strategies are expected to meet the growing demand for H2O2. Among the many reported technologies, electrocatalytic two-electron oxygen reduction (2e-ORR) can directly convert oxygen (O2) into H2O2 and is considered to be a promising alternative technology. For the electrocatalytic ORR process, O2 is first adsorbed on the catalyst and forms an *OOH intermediate through a one-step electron transfer. However, the thermodynamically competitive four-electron pathway makes it easier for *OOH to generate H2O through homolysis rather than homolysis to obtain H2O2 products. Some noble metals, such as PtAu and PaAu, are excellent catalysts for electrocatalytic 2e-ORR. Unfortunately, the high cost of the catalyst limits its large-scale application. Most of the non-precious metal catalysts and carbon materials reported so far tend to favor 4e-ORR, showing unsatisfactory H2O2 selectivity and stability. Therefore, designing high-performance catalysts to adjust the adsorption strength and breakage mode of *OOH is the key to improving the efficiency of 2e-ORR.
[0003] In recent years, single-atom catalysts (SACs) have been shown to have excellent oxygen reduction ability due to their high atomic utilization and independent adsorption sites. Unlike bridging adsorption, single-site adsorption in SACs can avoid the heterolytic cleavage of the OO bond in the *OOH transition state and promote the occurrence of the two-electron oxygen reduction process. In addition, the microenvironment of SACs catalysts, including the central atom, coordination number, and second coordination sphere (CSs), also has an important regulatory effect on the electron cloud density and intermediate separation of the active center. In theory, the ORR activity catalyzed by SACs depends on the interaction between the *OOH intermediate and the d orbital of the metal atom, which is believed to be the source of the electrocatalytic activity. Therefore, transition metals with unsaturated d orbitals are widely used in various electrocatalytic systems, while p-blocks with closed d shells are rarely used in electrocatalytic oxygen reduction processes. However, most single-atom catalysts based on d-block elements exhibit a thermodynamically easier four-electron process rather than a two-electron oxygen reduction process during electrocatalysis.
[0004] Therefore, in the process of preparing hydrogen peroxide by electrocatalytic two-electron oxygen reduction, how to design high-performance, low-cost catalysts to improve hydrogen peroxide selectivity and hydrogen peroxide production rate is an urgent problem that needs to be solved.
[0005] The present invention is proposed to solve the above-mentioned problems. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides a method for preparing a p-block element (P-block element) reinforced double single-atom material. The method of the present invention is the first to use p-block elements and traditional transition metals to cooperate with each other to prepare an excellent electrocatalytic two-electron oxygen reduction catalyst. In the preparation process of the catalyst, cobalt and gallium elements are introduced into the zeolite imidazolate precursor by ion exchange, and then the coordination environment of the catalyst is regulated by the introduction of sulfur species, and finally the p-block reinforced double single-atom catalyst is synthesized by high temperature annealing.
[0007] The present invention discloses a P-zone element-enhanced double single-atom catalyst, and a preparation method and application thereof, which belongs to the field of catalysts and solves the problem of poor selectivity of the conventional transition metal-based single-atom catalyst in the electrocatalytic two-electron oxygen reduction to produce hydrogen peroxide. The catalyst preparation process involved in the present invention is as follows: a cobalt salt, a gallium salt and a zinc salt are ion-exchanged with an organic ligand 2-methylimidazole to form a zeolite imidazole ester precursor, and then triisocyanuric acid is introduced into the above precursor as a sulfur source by chemical adsorption, and finally the target catalyst is synthesized by high-temperature calcination. The present invention also discloses the application of the catalyst in electrocatalytic two-electron oxygen reduction. The introduction of the gallium element improves the charge distribution of the conventional transition metal-based single-atom catalyst, thereby adjusting the fracture mode of the intermediate in the oxygen reduction process, greatly improving the selectivity of the oxygen reduction process and the rate of hydrogen peroxide production.
[0008] The present invention adopts the following technical solution:
[0009] The first aspect of the present invention provides a P-zone element-strengthened di-single-atom catalyst, wherein the P-zone element-strengthened di-single-atom catalyst has cobalt and gallium di-single-atoms as active components, and the cobalt and gallium di-single-atoms are anchored on a carbon substrate through asymmetric heteroatom coordination, and the content of cobalt and gallium di-single-atoms is 1.0-5.0wt%. The P-zone element-strengthened di-single-atom catalyst presents a porous regular dodecahedron structure at the microscopic level, with a specific surface area of 400-1000m2 / g and a pore size of 0.5-10nm.
[0010] The second aspect of the present invention provides a method for preparing the double single-atom catalyst strengthened by the P-zone element according to the first aspect of the present invention, which comprises the following steps:
[0011] (1) Preparing a zeolite imidazole ester precursor: dissolving 2-methylimidazole in a solvent to obtain a solution A; dissolving a cobalt salt, a gallium salt and a zinc salt in a solvent to obtain a solution B; stirring and mixing the solution A and the solution B at a certain temperature for a period of time, and then centrifuging, washing and drying to obtain a zeolite imidazole ester precursor;
[0012] (2) preparing a sulfur-doped zeolite imidazolate precursor: adding the zeolite imidazolate precursor obtained in step (1) into a solvent, adding a sulfur source thereto, stirring for sulfurization treatment, and then centrifuging and drying to obtain a sulfur-doped zeolite imidazolate precursor;
[0013] (3) Preparation of P-zone element-enhanced double single-atom catalyst: calcining the sulfur-doped zeolite imidazolate precursor obtained in step (2) at a certain temperature, cooling and further washing to obtain the P-zone element-enhanced double single-atom catalyst.
[0014] Preferably, the cobalt salt, gallium salt and zinc salt in step (1) are salts containing cobalt, gallium or zinc, and the salts used include acetate, nitrate and chloride;
[0015] The molar ratios of the cobalt salt, gallium salt, zinc salt and 2-methylimidazole used in step (1) are (1-10): (1-10): (1-10): 1 respectively;
[0016] The solvent in step (1) and step (2) includes one or a combination of water, methanol, dimethyl sulfoxide, acetonitrile and tetrahydrofuran.
[0017] Preferably, in step (1), the stirring and mixing reaction time of solution A and solution B is 6 to 24 hours, and the reaction temperature is 10 to 45°C.
[0018] Preferably, the speed of centrifugal collection of the sample in step (1) is 6000-11000 rpm, corresponding to a time of 2-10 min.
[0019] Preferably, in step (1), the drying time of the precursor after centrifugation and washing is 6 to 12 hours, and the drying temperature is 60 to 120°C.
[0020] Preferably, the sulfur source used in step (2) includes thiourea, triisocyanuric acid, elemental sulfur or sodium sulfide;
[0021] The mass ratio of the sulfur source to the zeolite imidazolate precursor used in step (2) is 1:5 to 1:20, and more preferably, the mass ratio of the sulfur source to the zeolite imidazolate precursor used is 1:20.
[0022] Preferably, in step (2), the vulcanization time is 0.5 to 3 hours, and the vulcanization temperature is 10 to 30°C.
[0023] Preferably, the sulfur-doped zeolite imidazole ester precursor prepared in step (3) is calcined in a tube furnace for 2 to 5 hours at a temperature of 600 to 1100°C.
[0024] The third aspect of the present invention provides an application of the double single-atom catalyst strengthened by the P-zone element as described in the first aspect of the present invention, wherein the double single-atom catalyst strengthened by the P-zone element is used as a catalyst for electrocatalytic two-electron oxygen reduction to produce hydrogen peroxide, so as to improve the hydrogen peroxide selectivity and the rate of hydrogen peroxide production.
[0025] The catalyst synthesized by the present invention is used in the electrocatalytic production of hydrogen peroxide. The technical solution adopted in the scheme is to adjust the pH of the solution to 13, the system voltage is between 0 and 1V (vs. RHE), the above catalyst is spin-coated on a ring disk electrode, and the test is carried out in a three-electrode system by rotating the disk electrode. In this process, oxygen is converted into hydrogen peroxide through a two-electron oxygen reduction process.
[0026] Compared with the prior art, the beneficial effects of the present invention are:
[0027] 1. The present invention synthesizes a catalyst with excellent two-electron oxygen reduction through simple ion coprecipitation, chemical adsorption and further high-temperature annealing. The catalyst preparation process of the method of the present invention is simple, easy to repeat, and has practical application value.
[0028] 2. The catalyst prepared by the present invention has cobalt and gallium diatoms as active components, and the cobalt and gallium diatoms are anchored on the carbon substrate through asymmetric heteroatom coordination. The content of cobalt and gallium diatoms is 1.0-5.0wt%, and it has a porous regular dodecahedral structure at the microscopic level, with a specific surface area of 400-1000m 2 / g, the pore size is 0.5-10nm, and the high specific surface area and rich micro-mesoporous structure of the catalyst provide sufficient active sites for the adsorption of oxygen in the oxygen reduction process.
[0029] 3. The present invention introduces p-block elements on the surface of traditional transition metal single-atom catalysts to regulate their microenvironment to construct a double single-atom catalyst, thereby converting the oxygen reduction process from a four-electron process to a two-electron process for producing hydrogen peroxide, thereby solving the problem of poor 2e-ORR performance of traditional transition metal single-atom catalysts. The catalyst of the present invention is used for electrocatalytic two-electron oxygen reduction to produce hydrogen peroxide, and has the advantages of high hydrogen peroxide selectivity and high hydrogen peroxide production rate, which is of far-reaching significance for expanding the application scenarios of p-block catalysts in the field of electrocatalysis.
[0030] The introduction of gallium improves the charge distribution of traditional transition metal single-atom catalysts, thereby regulating the breakage mode of intermediates in the oxygen reduction process, greatly improving the selectivity of the oxygen reduction process and the rate of hydrogen peroxide production.
[0031] 4. The present invention combines the DACs catalysts under different microenvironments with the 2e-ORR efficiency of electrocatalysis, which has guiding significance for revealing the structure-performance relationship of DACs catalysts.
[0032] 5. The p-block elements with unsaturated p orbitals can form bonds with O groups through pp conjugation to adjust the charge density of adjacent transition metal atoms. Based on this, the present invention uses p-block elements to optimize the local electron density and *OOH adsorption process of traditional transition metal single atom catalysts, which has guiding significance for revealing the structure-performance relationship of SACs catalysts and improving the 2e-ORR selectivity of SACs catalysts. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below in conjunction with specific implementation methods. It should be noted that the following examples are only used to illustrate and explain the present invention in detail, and the application scope of the present invention is not limited by the conditions in the examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a flow chart of the preparation of the p-block enhanced double single atom catalyst of the present invention.
[0035] Figure 2 This is the XRD diagram of the p-block enhanced double single atom catalyst synthesized in Example 1 of the present invention.
[0036] Figure 3 This is a SEM image of the p-block enhanced double single-atom catalyst synthesized in Example 1 of the present invention.
[0037] Figure 4 It is a diagram of the specific surface area and pore size distribution of the p-block enhanced double single atom catalyst synthesized in Example 1 of the present invention.
[0038] Figure 5 This is an AC-TEM image of the p-block enhanced double single-atom catalyst synthesized in Example 1 of the present invention.
[0039] Figure 6 It is the EXAF fitting diagram of the p-block enhanced double single-atom catalyst synthesized in Example 1 of the present invention.
[0040] Figure 7 It is a cyclic voltammetry curve of the p-block enhanced double single-atom catalyst synthesized in Example 1 of the present invention under nitrogen and oxygen atmospheres.
[0041] Figure 8It is a graph of hydrogen peroxide selectivity of the p-block enhanced double single-atom catalysts synthesized in Example 1 and Comparative Examples 1-3 of the present invention.
[0042] Fig. 9 This is a diagram of the cumulative concentration of hydrogen peroxide in the electrocatalytic two-electron oxygen reduction process of the p-block enhanced double single-atom catalyst synthesized in Example 1 of the present invention.
[0043] Fig.10 Graph showing the selectivity of electrocatalytic two-electron oxygen reduction of the p-block enhanced double single-atom catalysts synthesized in Examples 2 to 6 of the present invention. DETAILED DESCRIPTION
[0045] The present invention is further described below by way of examples, which are not limited to the examples. Experimental methods without specific conditions specified in the examples are generally carried out under conventional conditions and conditions described in the manual, or under conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used are all commercially available unless otherwise specified.
[0046] Example 1: Figure 1 The process described.
[0047] Step 1: Prepare zeolite imidazole ester precursor. Dissolve 3.08g of 2-methylimidazole in 100ml of methanol to obtain solution A; dissolve 1.365g of cobalt nitrate hexahydrate, 2.79g of zinc nitrate hexahydrate and 0.136g of gallium nitrate in 50ml of methanol to obtain solution B; mix solution A and solution B at 25°C, stir at 500rpm for 18h, centrifuge at 1000rpm for 5min, wash with methanol 3 times, and dry in an oven at 60°C for 12h to obtain zeolite imidazole ester precursor.
[0048] Step 2: Preparation of sulfur-doped zeolite imidazole ester precursor. 100 mg of the precursor obtained in step (1) was added to 30 ml of methanol, and 6 mg of triisocyanuric acid sulfur source was added thereto. The mixture was stirred at 500 rpm for 0.5 h at 25° C., centrifuged at 1000 rpm for 5 min, and washed with methanol 3 times to obtain a sulfur-doped zeolite imidazole ester precursor.
[0049] Step 3: Preparation of P-zone element-enhanced double single-atom catalyst. The precursor obtained in step (2) was calcined at 950°C at 5°C / min in a nitrogen atmosphere for 3 h, and after cooling, it was washed with ethanol and water for 3 times, and then dried in an oven at 60°C for 12 h to obtain the target catalyst, which was named CoGa-NS-C. The contents of cobalt and gallium double single atoms in the catalyst were 3.1wt% and 2.8wt%, respectively.
[0050] like Figure 2 As shown, the X-ray diffraction test results show that the prepared double single-atom catalyst only has typical peaks of carbon materials, and no metal particles are present.
[0051] like Figure 3 As shown, the scanning electron microscopy test results show that the synthesized double single-atom catalyst maintains the regular dodecahedral structure of zeolite imidazolate and has a rich pore structure in the material.
[0052] like Figure 4 As shown in Figure 2, the nitrogen adsorption-desorption curves show that the specific surface area of the synthesized double single-atom catalyst is 400-1000m 2 / g, the pore size is 0.5-10nm, and the rich pore structure greatly promotes the mass transfer in the oxygen reduction process.
[0053] like Figure 5 As shown, the spherical aberration electron microscopy test results indicate that the metal atoms in the synthesized double single-atom catalyst exist in the form of single atoms.
[0054] like Figure 6 As shown, the microscopic coordination structure of cobalt and gallium double single atoms was analyzed by synchrotron radiation, which showed that the synthesized double single atom catalyst exists through the neighboring CoN3S1-GaN4 coordination structure.
[0055] like Figure 7 As shown, by comparing the cyclic voltammetry curves under nitrogen and oxygen atmospheres, it can be seen that the synthesized cobalt and gallium double single-atom catalysts have obvious redox peaks in the oxygen atmosphere, confirming the occurrence of the reaction.
[0056] like Figure 8 As shown, the catalyst of Example 1 exhibits excellent electrocatalytic two-electron oxygen reduction ability, and there is an obvious redox peak in the cyclic voltammetry curve in the presence of oxygen; during the test of the rotating disk, the selectivity of the oxygen reduction process is greater than 90%, showing excellent catalytic performance.
[0057] like Fig. 9 As shown, through the current test in the H cell, it can be determined that the synthesized cobalt and gallium double single atoms have excellent hydrogen peroxide generation rate and stability.
[0058] Embodiment 2:
[0059] Step 1: Prepare zeolite imidazole ester precursor. Dissolve 1.54g of 2-methylimidazole in 100ml of methanol to obtain solution A; dissolve 1.365g of cobalt nitrate hexahydrate, 2.79g of zinc nitrate hexahydrate and 0.136g of gallium nitrate in 50ml of methanol to obtain solution B; mix solution A and solution B at 25°C, stir at 500rpm for 18h, centrifuge at 1000rpm for 5min, wash with methanol 3 times, and dry in an oven at 60°C for 12h to obtain zeolite imidazole ester precursor.
[0060] Step 2: Preparation of sulfur-doped zeolite imidazole ester precursor. 100 mg of the precursor obtained in step (1) was added to 30 ml of methanol, and 6 mg of triisocyanuric acid was added thereto. The mixture was stirred at 500 rpm for 0.5 h at 25° C., centrifuged at 1000 rpm for 5 min, and washed with methanol three times to obtain a sulfur-doped zeolite imidazole ester precursor.
[0061] Step 3: Preparation of P-zone element-enhanced double single-atom catalysts. The precursor obtained in step (2) was calcined at 950°C at 5°C / min in a nitrogen atmosphere for 3 h, and after cooling, it was washed with ethanol and water for 3 times respectively, and then dried in an oven at 60°C for 12 h to obtain the target catalyst.
[0062] Embodiment 3:
[0063] Step 1: Prepare zeolite imidazole ester precursor. Dissolve 3.08g of 2-methylimidazole in 100ml of methanol to obtain solution A; dissolve 1.365g of cobalt nitrate hexahydrate, 2.79g of zinc nitrate hexahydrate and 0.136g of gallium nitrate in 50ml of methanol to obtain solution B; mix solution A and solution B at 25°C, stir at 500rpm for 18h, centrifuge at 1000rpm for 5min, wash with methanol 3 times, and dry in an oven at 60°C for 12h to obtain zeolite imidazole ester precursor.
[0064] Step 2: Preparation of sulfur-doped zeolite imidazole ester precursor. 100 mg of the precursor obtained in step (1) was added to 30 ml of methanol, and 6 mg of thiourea was added thereto. The mixture was stirred at 500 rpm for 0.5 h at 25° C., centrifuged at 1000 rpm for 5 min, and washed with methanol three times to obtain a sulfur-doped zeolite imidazole ester precursor.
[0065] Step 3: Preparation of P-zone element-enhanced double single-atom catalysts. The precursor obtained in step (2) was calcined at 950°C at 5°C / min in a nitrogen atmosphere for 3 h, and after cooling, it was washed with ethanol and water for 3 times respectively, and then dried in an oven at 60°C for 12 h to obtain the target catalyst.
[0066] Embodiment 4:
[0067] Step 1: Prepare zeolite imidazole ester precursor. Dissolve 3.08g of 2-methylimidazole in 100ml of methanol to obtain solution A; dissolve 1.365g of cobalt nitrate hexahydrate, 2.79g of zinc nitrate hexahydrate and 0.136g of gallium nitrate in 50ml of methanol to obtain solution B; mix solution A and solution B at 25°C, stir at 500rpm for 18h, centrifuge at 1000rpm for 5min, wash with methanol 3 times, and dry in an oven at 60°C for 12h to obtain zeolite imidazole ester precursor.
[0068] Step 2: Preparation of sulfur-doped zeolite imidazole ester precursor. 100 mg of the precursor obtained in step (1) was added to 30 ml of methanol, and 6 mg of thiourea was added thereto. The mixture was stirred at 500 rpm for 0.5 h at 25° C., centrifuged at 1000 rpm for 5 min, and washed with methanol three times to obtain a sulfur-doped zeolite imidazole ester precursor.
[0069] Step 3: Preparation of P-zone element-enhanced double single-atom catalysts. The precursor obtained in step (2) was calcined at 800°C at 5°C / min in a nitrogen atmosphere for 3 h, and after cooling, it was washed with ethanol and water for 3 times respectively, and then dried in an oven at 60°C for 12 h to obtain the target catalyst.
[0070] Embodiment 5:
[0071] Step 1: Prepare zeolite imidazole ester precursor. Dissolve 1.54g of 2-methylimidazole in 100ml of methanol to obtain solution A; dissolve 1.365g of cobalt nitrate hexahydrate, 2.79g of zinc nitrate hexahydrate and 0.136g of gallium nitrate in 50ml of methanol to obtain solution B; mix solution A and solution B at 25°C, stir at 500rpm for 18h, centrifuge at 1000rpm for 5min, wash with methanol 3 times, and dry in an oven at 60°C for 12h to obtain zeolite imidazole ester precursor.
[0072] Step 2: Preparation of sulfur-doped zeolite imidazole ester precursor. 100 mg of the precursor obtained in step (1) was added to 30 ml of methanol, and 6 mg of thiourea was added thereto. The mixture was stirred at 500 rpm for 0.5 h at 25° C., centrifuged at 1000 rpm for 5 min, and washed with methanol three times to obtain a sulfur-doped zeolite imidazole ester precursor.
[0073] Step 3: Preparation of P-zone element-enhanced double single-atom catalysts. The precursor obtained in step (2) was calcined at 800°C at 5°C / min in a nitrogen atmosphere for 3 h, and after cooling, it was washed with ethanol and water for 3 times respectively, and then dried in an oven at 60°C for 12 h to obtain the target catalyst.
[0074] Embodiment 6:
[0075] Step 1: Prepare zeolite imidazole ester precursor. Dissolve 3.08g of 2-methylimidazole in 100ml of methanol to obtain solution A; dissolve 1.365g of cobalt chloride hexahydrate, 2.79g of zinc chloride and 0.136g of gallium chloride in 50ml of methanol to obtain solution B; mix solution A and solution B at 25°C, stir at 500rpm for 18h, centrifuge at 1000rpm for 5min, wash with methanol 3 times, and then dry in an oven at 60°C for 12h to obtain zeolite imidazole ester precursor.
[0076] Step 2: Preparation of sulfur-doped zeolite imidazole ester precursor. 100 mg of the precursor obtained in step (1) was added to 30 ml of methanol, and 6 mg of triisocyanuric acid was added thereto. The mixture was stirred at 500 rpm for 0.5 h at 25° C., centrifuged at 1000 rpm for 5 min, and washed with methanol three times to obtain a sulfur-doped zeolite imidazole ester precursor.
[0077] Step 3: Preparation of P-zone element-enhanced double single-atom catalysts. The precursor obtained in step (2) was calcined at 800°C at 5°C / min in a nitrogen atmosphere for 3 h, and after cooling, it was washed with ethanol and water for 3 times respectively, and then dried in an oven at 60°C for 12 h to obtain the target catalyst.
[0078] like Fig.10 As shown in Examples 2-6, it can be seen that different metal contents have a great influence on the selectivity of the catalyst for electrocatalytic two-electron oxygen reduction. Figure 8 It can be seen that Example 1 exhibits the most excellent two-electron oxygen reduction selectivity performance.
[0079] Comparative Example 1
[0080] Step 1: Prepare zeolite imidazole ester precursor. Dissolve 3.08g of 2-methylimidazole in 100ml of methanol to obtain solution A; dissolve 1.365g of cobalt nitrate hexahydrate, 2.79g of zinc nitrate hexahydrate and 0.136g of gallium nitrate in 50ml of methanol to obtain solution B; mix solution A and solution B at 25°C, stir at 500rpm for 18h, centrifuge at 1000rpm for 5min, wash with methanol 3 times, and dry in an oven at 60°C for 12h to obtain zeolite imidazole ester precursor.
[0081] Step 2: Prepare a double single-atom catalyst strengthened by P-zone elements. The precursor obtained in step (2) was calcined at 950°C at 5°C / min in a nitrogen atmosphere for 3 hours, and after cooling, it was washed with ethanol and water for 3 times respectively, and then dried in an oven at 60°C for 12 hours to obtain the target catalyst, which was named CoGa-NC.
[0082] The catalyst preparation process does not involve the process of regulating its microenvironment through sulfidation adsorption.
[0083] Comparative Example 2
[0084] Step 1: Preparation of zeolite imidazole ester precursor. Dissolve 3.08g of 2-methylimidazole in 100ml of methanol to obtain solution A; dissolve 1.365g of cobalt nitrate hexahydrate and 2.79g of zinc nitrate hexahydrate in 50ml of methanol to obtain solution B; mix solution A and solution B at 25°C, stir at 500rpm for 18h, centrifuge at 1000rpm for 5min, wash with methanol 3 times, and dry in an oven at 60°C for 12h to obtain zeolite imidazole ester precursor.
[0085] Step 2: Prepare a double single-atom catalyst strengthened by P-zone elements. The precursor obtained in step (2) was calcined at 950°C at 5°C / min in a nitrogen atmosphere for 3 h, and after cooling, it was washed with ethanol and water for 3 times respectively, and then dried in an oven at 60°C for 12 h to obtain the target catalyst, which was named Co-NC.
[0086] During the preparation of the catalyst, there is no process of regulating its microenvironment through sulfidation adsorption and no gallium species are introduced. It is a single-atom catalyst.
[0087] Comparative Example 3
[0088] Step 1: Prepare zeolite imidazole ester precursor. Dissolve 3.08g of 2-methylimidazole in 100ml of methanol to obtain solution A; dissolve 2.79g of zinc nitrate hexahydrate and 0.136g of gallium nitrate in 50ml of methanol to obtain solution B; mix solution A and solution B at 25°C, stir at 500rpm for 18h, centrifuge at 1000rpm for 5min, wash with methanol 3 times, and then dry in an oven at 60°C for 12h to obtain zeolite imidazole ester precursor.
[0089] Step 2: Prepare a double single-atom catalyst strengthened by P-zone elements. The precursor obtained in step (1) was calcined at 950°C at 5°C / min in a nitrogen atmosphere for 3 hours, and after cooling, it was washed with ethanol and water for 3 times respectively, and then dried in an oven at 60°C for 12 hours to obtain the target catalyst, which was named Ga-NC.
[0090] In the preparation process of the catalyst, there is no process of regulating its microenvironment through sulfide adsorption and no cobalt species are introduced. It is a single-atom catalyst.
[0091] The above description is only used to introduce the specific implementation methods of the present invention in detail, but the technical solution proposed by the present invention is not limited to the above method. Without departing from the basic principles of the present technology, equivalent modifications and changes made by those skilled in the art to the technology proposed by the present invention should be included in the scope of the claims of the present invention.
Claims
1. A double single-atom catalyst strengthened by P-zone elements, characterized in that: The P-zone element-enhanced double single-atom catalyst has cobalt and gallium double single atoms as active components, and the cobalt and gallium double single atoms are anchored on the carbon substrate through asymmetric heteroatom coordination. The content of cobalt and gallium double single atoms is 1.0-5.0wt%. The P-zone element-enhanced double single-atom catalyst presents a porous regular dodecahedron structure with a specific surface area of 400-1000m 2 / g, pore size is 0.5~10nm.
2. A method for preparing the P-zone element-enhanced double single-atom catalyst according to claim 1, characterized in that: It includes the following steps: (1) Preparing a zeolite imidazole ester precursor: dissolving 2-methylimidazole in a solvent to obtain a solution A; dissolving a cobalt salt, a gallium salt and a zinc salt in a solvent to obtain a solution B; The solution A and the solution B are stirred and mixed to react for a period of time at a certain temperature, and then centrifuged, washed and dried to obtain a zeolite imidazole ester precursor; (2) preparing a sulfur-doped zeolite imidazolate precursor: adding the zeolite imidazolate precursor obtained in step (1) into a solvent, adding a sulfur source thereto, stirring for sulfurization treatment, and then centrifuging and drying to obtain a sulfur-doped zeolite imidazolate precursor; (3) Preparation of P-zone element-enhanced double single-atom catalyst: calcining the sulfur-doped zeolite imidazolate precursor obtained in step (2) at a certain temperature, cooling and further washing to obtain the P-zone element-enhanced double single-atom catalyst.
3. The preparation method according to claim 2, characterized in that: In step (1), the cobalt salt, gallium salt and zinc salt are salts containing cobalt, gallium or zinc, and the salts used include acetate, nitrate and chloride; The molar ratios of the cobalt salt, gallium salt, zinc salt and 2-methylimidazole used in step (1) are (1-10): (1-10): (1-10): 1 respectively; The solvent in step (1) and step (2) includes one or a combination of water, methanol, dimethyl sulfoxide, acetonitrile and tetrahydrofuran.
4. The preparation method according to claim 2, characterized in that: In step (1), the stirring and mixing of solution A and solution B is carried out for 6 to 24 hours, and the reaction temperature is 10 to 45°C.
5. The preparation method according to claim 2, characterized in that: The speed of the sample centrifugal collection in step (1) is 6000-11000 rpm, corresponding to a time of 2-10 min.
6. The preparation method according to claim 2, characterized in that: In step (1), the drying time is 6 to 12 hours and the drying temperature is 60 to 120°C.
7. The preparation method according to claim 2, characterized in that: The sulfur source used in step (2) includes thiourea, triisocyanuric acid, elemental sulfur or sodium sulfide; The mass ratio of the sulfur source to the zeolite imidazole ester precursor used in step (2) is 1:5 to 1:
20.
8. The preparation method according to claim 2, characterized in that: In step (2), the vulcanization time is 0.5 to 3 hours, and the vulcanization temperature is 10 to 30°C.
9. The preparation method according to claim 2, characterized in that: In step (3), the calcination time is 2 to 5 hours, and the calcination temperature is 600 to 1100°C.
10. An application of the double single-atom catalyst strengthened by P-zone elements as claimed in claim 1, characterized in that: The double single-atom catalyst strengthened by the P-zone element is used as a catalyst for producing hydrogen peroxide by electrocatalytic two-electron oxygen reduction, so as to improve the selectivity of hydrogen peroxide and the rate of producing hydrogen peroxide.
Citation Information
Patent Citations
Cobalt sulfide loaded NiGa-LDH electrode material with polyhedral structure and preparation method and application of cobalt sulfide loaded NiGa-LDH electrode material
CN115274310A
Carbon-based gallium monatomic material for synthesizing hydrogen peroxide through electro-catalytic oxygen reduction and preparation method and application of carbon-based gallium monatomic material
CN116377499A